INFORMATION PREDICTABILITY IN THE PROBLEM OF PARAMETER ESTIMATION ON THE BACKGROUND OF NON-STATIONARY PROCESSES - A. V. Ausiannikau; V. M. Kozel (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The necessary theoretical information for algorithms estimating unknown parameters useful for background noise nonstationary stochastic processes is given. The relationship of information predictability stochastic process and evaluation is shown.